Advanced Energetic Materials: Testing and Modeling (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
To accelerate the potential applications, various works focused on the physical and chemical characteristics through theory, experiments, and simulations of advanced energetic materials (AEMs), including nano-scale energetic materials (nEMs) and micro-scale energetic materials (mEMs). This Special Issue collected comprehensive knowledge on materials synthesis, characterization, combustion, mechanical, detonation, and safety. This Special Issue, Advanced Energetic Materials: Testing and Modeling, explores innovative EMs and EMs ingredients and formulations tests and models. It collected contributions covering recent progress and models of energetic materials in chemical propulsion. Attention was focused on the design, model, properties, and state-of-the-art of this class of thermochemical propulsion devices. A total of 13 papers were selected for publication after a standard peer review process, which summarizes the most recent achievements of famous research groups. Participation of young authors with novel/innovative concepts was especially encouraged, of course, with the assistance of their supervisors.